The Glass Closet: Perceptions of Homosexuality in Intercollegiate Sport - Jordan Bass; Robin Hardin; Elizabeth A. Taylor (Journal of Applied Sports Management, 2015)
A mixed-methods approach was used to examine the perceptions and prevalence of open homosexuality in intercollegiate sport in the United States. Universityhosted biographies of NCAA Bowl Championship Series (BCS) head coaches were coded to determine the frequency of head coaches listing a wife, husband, and same-sex partner (Calhoun, LaVoi, & Johnson, 2011). These findings were paired with interviews of five college coaches exploring their feelings toward the culture surrounding homosexuality, by players, coaches, and administrators, at their university. Only one coach of more than 1,000 was identified as having a same-sex partner in university-sponsored coaching biographies. Interview findings revealed collegiate athletics is not as accepting to homosexuality even though societal acceptance is increasing.
Keywords: gender; homosexuality; coaching biographies; institutional policy; coaching; college sport